2016
DOI: 10.1371/journal.pone.0162780
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Free-Floating Plants Is Strongly Driven by Previously Experienced Phosphorus Concentrations in the Water Column

Abstract: Nutrients can determine the outcome of the competition between different floating plant species. The response of floating plants to current phosphorus levels may be affected by previously experienced phosphorus concentrations because some species have the ability to store excess phosphorus for later use. This might have an impact on their competition. Here, we investigate the effect of previous and actual phosphorus concentrations on the growth rate of free-floating plant species (Azolla filiculoides, Lemna mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In general, distribution of a species depends on the match of an array of physico-chemical parameters with the specific environmental requirements of the species (Santamaría, 2002 ). For example, a study by Peeters et al ( 2016 ) revealed the relative importance of phosphorus for growth and competitiveness of free-floating macrophytes, and the presence of many species of aquatic macrophytes is associated with eutrophic conditions (Carbiener et al, 1990 ). The study presented here revealed a substantial gradient of light and nutrients across the 24 natural ponds in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…In general, distribution of a species depends on the match of an array of physico-chemical parameters with the specific environmental requirements of the species (Santamaría, 2002 ). For example, a study by Peeters et al ( 2016 ) revealed the relative importance of phosphorus for growth and competitiveness of free-floating macrophytes, and the presence of many species of aquatic macrophytes is associated with eutrophic conditions (Carbiener et al, 1990 ). The study presented here revealed a substantial gradient of light and nutrients across the 24 natural ponds in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a lack of research concerning the influence of species interaction on duckweed resistance to metal pollution. Previous studies suggest that species interactions in duckweeds can influence growth rates (Clatworthy & Harper, 1962;Gopal & Goel, 1993;Peeters et al, 2016). Here, we hypothesized that the presence of a second species in a mixed setting could increase heavy metal tolerance because of facilitation.…”
Section: Introductionmentioning
confidence: 86%
“…The general composition of the solution was similar to the quality of natural surface waters where Azolla is abundant (Supplementary Table S1 ). After sufficient Azolla biomass had been produced in the greenhouse for 30 days 37 , the plants were pretreated for 10 days in larger basins without harvesting to minimize P history effects 13 . Nutrient solutions were replaced 3 times a week.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient solutions were replaced 3 times a week. After this period 13 , 7.5 g (surface cover of 90%) of carefully dry-blotted A. filiculoides was transferred to a 1 l glass aquarium (10 cm × 10 cm × 12 cm; L × W × H; 750 g FW m −2 ), which was continuously fed by the same nutrient solution (pH = 7.3) as during the acclimatization period, at a rate of 1 l d −1 using peristaltic pumps (Masterflex L/S; Cole-Palmer, Chicago, IL, USA). Nutrient concentrations were checked biweekly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation